PENGARUH BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MENURUT EKONOMI ISLAM (STUDY PADA CAFE AMY STEAK & SHAKE SIAK) - Hendri, Hendri (STAI Sulthan Syarif Hasyim, 2025)
This study aims to determine the influence of brand image (X) on consumer purchasing decisions (Y) according to Islamic economics (a study at Amy Steak & Shake Siak Cafe). The sample used in this study consisted of 98 consumers. This is a quantitative study, and the sampling method used in this study is Non-Probability Sampling, specifically Incidental Sampling, which is a technique for determining samples based on spontaneity, meaning that anyone who happens to meet the researcher and meets the characteristics (traits) can be used as a sample (respondent). The data analysis method used in this study was Simple Linear Regression Analysis, and the statistical calculations were performed using SPSS 25 software. Based on the test results, it was concluded that Brand Image (X) significantly influences consumer purchasing decisions (Y). This is evidenced by the sig. value of 0.000 < 0.05 and the t-value of 3.505 with a Sig X value of 0.001. The null hypothesis (Ho) is accepted if the t-value is less than the critical t-value (1.667 < 3.505), indicating that Brand Image (X) has an influence on consumer purchasing decisions (Y). The influence of the Brand Image (X) variable on purchasing decisions (Y) is interpreted as moderate or of moderate influence. This can be seen from the coefficient of determination with R-squared (r²) = 0.576 or 57%, meaning that the influence of the Brand Image variable (X) on the purchase decision (Y) is 57%, while the remaining 43% is determined by other factors not included in this study.